A Case Study On Uni-President Enterprises Corp - Min, Wang (2005)
The subject of this case study on Uni-president Enterprises Corp was triggered by the Chinese food situation and introduced a systematic way of verifying the most relevant transformations that a multinational company needs to perform to migrate to the more competitive shape of the global model. This case study will provide valuable information on the food industry and Recruitment Company's operation.